HUBUNGAN ANTARA TINGKAT PENDAPATAN DAN PILIHAN KONSUMSI BERDASARKAN TEORI ORDINAL - Icha Lesmana; Iyana Tasya Br Ginting; Julia Dewi Sari Siahaan; Reza Rumapea; Yesica Kris Cinta Saragih (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to analyze the relationship between income levels and consumer consumption choicesbased on ordinal theory. In this theory, consumer preferences are illustrated through indifference curves and budget lines, without the need to measure utility quantitatively. Using a qualitative descriptive approach and literature study methods, this research finds that changes in income levels affect consumption realization, even though consumer preferences remain stable. A simulation of the consumption of two goods (rice and chicken) shows that an increase in income allows consumers to move to a higher indifference curve, reflecting a greater level of satisfaction. These results reinforce the relevance of ordinal theory in explaining consumption behavior in dynamic economic conditions.